2018
DOI: 10.1098/rstb.2017.0377
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectomics from neural dynamics: probabilistic graphical models for neuronal network ofCaenorhabditis elegans

Abstract: We propose an approach to represent neuronal network dynamics as a probabilistic graphical model (PGM). To construct the PGM, we collect time series of neuronal responses produced by the neuronal network and use singular value decomposition to obtain a low-dimensional projection of the time-series data. We then extract dominant patterns from the projections to get pairwise dependency information and create a graphical model for the full network. The outcome model is a functional connectome that captures how st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…Modeling the dynamics of the neural network is possible by combining the known structural connectome data of C. elegans with a physiologically model of a neuron [74]. Models such as probabilistic graphical models (PGMs), use known circuits of repetitive behavior, (Figure 2D), to predict responses to novel situations [75,76].…”
Section: Technologies Employed To Unravel the Functional Connectomementioning
confidence: 99%
“…Modeling the dynamics of the neural network is possible by combining the known structural connectome data of C. elegans with a physiologically model of a neuron [74]. Models such as probabilistic graphical models (PGMs), use known circuits of repetitive behavior, (Figure 2D), to predict responses to novel situations [75,76].…”
Section: Technologies Employed To Unravel the Functional Connectomementioning
confidence: 99%
“…In addition, the model allows for computational clamping of neurons by external current injection. We previously observed that injection of constant current into sensory neurons, e.g., the posterior PLM mechanosensory neurons, evoke oscillatory neural responses in some motor neurons producing low dimensional attractor-like dynamics and transient dynamics with longer timescales than the intrinsic neural dynamics (24,31).…”
Section: Resultsmentioning
confidence: 99%
“…Being closer to the realistic neuronal system, dynome studies have more potential to reveal neural pathways and functionalities of the network (Bargmann and Marder, 2013 ; Sporns and Bullmore, 2014 ; Liu et al, 2018 ). However, they also introduce challenges in finding appropriate methods for efficient studies of network capabilities (Mucha et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%